2017
DOI: 10.3390/ijms18081661
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Promoter Analysis of ChiIV3, a Chitinase of Pepper Plant, in Response to Phytophthora capsici Infection

Abstract: Despite the involvement of many members of the chitinase family in plant immunity, the precise functions of the majority of the members remain poorly understood. Herein, the gene ChiIV3 in Capsicum annuum encoding a chitinase protein containing a chitin binding domain and targeting to the plasma membrane was found to be induced by Phytophthora capsici inoculation (PCI) and applied chitin treatment. Besides its direct inhibitory effect on growth of Phytophthora capsici (P. capsici), ChiIV3 was also found by vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 59 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…The subcellular localization of CBP members may show their associated functions. Some CBP genes in other plants such as ScChiI1 have been localized in the cytoplasm and the plasma membrane (Su et al, 2015) and ChiIV3 in the plasma membrane (Liu Z. et al, 2017). In Oryza sativa, CBP proteins are located in cytoplasm and mitochondria and are thought to be associated with the thylakoid membrane under heat stress (Xu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcellular localization of CBP members may show their associated functions. Some CBP genes in other plants such as ScChiI1 have been localized in the cytoplasm and the plasma membrane (Su et al, 2015) and ChiIV3 in the plasma membrane (Liu Z. et al, 2017). In Oryza sativa, CBP proteins are located in cytoplasm and mitochondria and are thought to be associated with the thylakoid membrane under heat stress (Xu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Cis-regulatory elements (1500bp upstream region) were searched by PlantCARE online server 3 (Lescot et al, 2002). Publicly available transcriptomic data of root and leaf for pepper cultivar "Zunla" were obtained from the online server 4 , and the genomic database was generated by following Liu Z. et al (2017) and Yu et al (2017) method and the data were presented in line-graphs (CaChiVI2 sequence shown in Supplementary Table S1).…”
Section: Sequence Alignment and In Silico Analysismentioning
confidence: 99%
“…Furthermore, ChiIV3 is a positive regulator of plant cell death and triggers defense signaling and upregulation of pathogenesis related genes against P . capsici infection ( Liu et al, 2017 ). Interestingly, there appears to be several different types of R genes in Capsicum .…”
Section: Strategiesmentioning
confidence: 99%
“…Cumulatively, these are responsible for an approximately 30% loss in global crop production at pre- and post-harvest levels [ 2 ]. All plant pathogens continuously challenge the host immune system [ 3 ], so, to counteract multifarious infection types, plants have evolved an array of defense responses by activating or suppressing a number of genes [ 4 , 5 , 6 ]. In succeeding events of pathogen attack, plants recognize a cascade of PAMPs or DAMPs (host danger-associated molecular patterns) [ 3 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…All plant pathogens continuously challenge the host immune system [ 3 ], so, to counteract multifarious infection types, plants have evolved an array of defense responses by activating or suppressing a number of genes [ 4 , 5 , 6 ]. In succeeding events of pathogen attack, plants recognize a cascade of PAMPs or DAMPs (host danger-associated molecular patterns) [ 3 , 7 , 8 , 9 ]. Cell-surface-based PRRs (pattern-recognition receptors), e.g., FLS2, EF-Tu, LYK5, and CERK1, perceive pathogens, i.e., bacteria- and fungi-triggered PAMPs or DAMPs [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%